Evaluating The Acceptance Of Datawarehouse By End-Users Using The Technology Acceptance Model A Case Study On Maybank Berhad - Ramaiah, Shobah Atchitha (2005)
This thesis focuses on the evaluation on the acceptance of data warehouse by end users, adapting the Technology Acceptance Model (TAM), in Maybank Berhad, a leading Malaysian bank. This study will lead to identify whether this EDW serves its purpose as set out by the management, from the viewpoints or perception of the end users. This study will give valuable insights to the EDW management team, to make proper future plans for this technology in terms of expansion, usage, importance etc.